2022
DOI: 10.1080/01916122.2022.2127957
|View full text |Cite
|
Sign up to set email alerts
|

Honey-producing bee–pollen–vegetation relationships in the West Coast and Western Ghats of India

Abstract: The ecosystem services offered by honey-producing bees are highly significant for the fertilization of flowers to produce fruits and seeds. The pollen found on bees and in honeycombs and honey represents the type of vegetation visited by the bees. The pollen diversity of honeycombs built by four honey-producing bees of the west coast and Western Ghats of India was evaluated to identify the floral sources. A spectrum of 54 pollen types (belonging to 52 genera in 34 families) was identified on the west coast, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…This result was supported by a high number of pollen taxa found in the honey from forestagriculture-dominated landscapes (FL) in Kerinci, which revealed more diversified pollen collected by the foraging honey bees with a total of sixteen pollen types (Figures 4B, 6C, D). Our result is concordant with the honey of A. dorsata produced in the more diverse vegetation of deciduous forests in Western Ghats, India, which contains a more diverse pollen type compared to the honey produced in less diverse vegetation in West Coast India (Hegde et al, 2023). No predominant pollen taxon was found in the FL Kerinci.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This result was supported by a high number of pollen taxa found in the honey from forestagriculture-dominated landscapes (FL) in Kerinci, which revealed more diversified pollen collected by the foraging honey bees with a total of sixteen pollen types (Figures 4B, 6C, D). Our result is concordant with the honey of A. dorsata produced in the more diverse vegetation of deciduous forests in Western Ghats, India, which contains a more diverse pollen type compared to the honey produced in less diverse vegetation in West Coast India (Hegde et al, 2023). No predominant pollen taxon was found in the FL Kerinci.…”
Section: Discussionsupporting
confidence: 85%
“…An experimental study of honey bee A. mellifera revealed that the amount and rate of pollen and nectar collection were positively correlated with the individual foraging experience of the bees (Klein et al, 2019). In addition, relationship analysis between the pollen contained in honey and vegetation types in the West Coast (WC) and Western Ghats (WG), India, revealed that floral resources also affected pollen concentration in honey (Hegde et al, 2023). Apis indica honey from the more diverse vegetation of the WG, showed a higher pollen concentration compared to those from the WC, which has less diverse vegetation (Hegde et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The east coast is sandy and the west coast is more or less rocky, which further indicates that the east coast of India is more vulnerable to coastal processes, whereas the western coastal regions are somewhere still rigid to coastal forcing [17]. Apart from different geological settings, the west coast and the Western Ghats are home to many endangered species of flora and fauna [33,34]. At the same time, the east coast of the study area has heavy commercial and economic activities because of the presence of ports and large cities along and near the coast [35].…”
Section: Introductionmentioning
confidence: 99%